1995
DOI: 10.1128/mcb.15.11.5849
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a G2 Checkpoint in p53-Independent Apoptosis Induction by X-Irradiation

Abstract: The p53 tumor suppressor gene is thought to be required for the induction of programmed cell death (apoptosis) initiated by DNA damage. We show here, however, that the human promyelocytic leukemia cell line HL-60, which is known to be deficient in p53 because of large deletions in the p53 gene, can be induced to undergo apoptosis following X-irradiation. We demonstrate that the decision to undergo apoptosis in this cell line appears to be made at a G 2 checkpoint. In addition, we characterize an HL-60 variant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 59 publications
4
76
0
1
Order By: Relevance
“…In striking contrast to the parental cells, which were very apoptotic sensitive, HCW-2 cells were highly resistant to the apoptotic effects of many treatments (Han et al, 1995;1996a). The resistance of HCW-2 cells to diverse apoptotic treatments suggested that it was unlikely that the cells were defective in multiple individual pathways for the transduction of different apoptotic signals, but rather were defective in a common event(s) that was induced by many apoptotic signal transduction pathways.…”
Section: Introductionmentioning
confidence: 98%
“…In striking contrast to the parental cells, which were very apoptotic sensitive, HCW-2 cells were highly resistant to the apoptotic effects of many treatments (Han et al, 1995;1996a). The resistance of HCW-2 cells to diverse apoptotic treatments suggested that it was unlikely that the cells were defective in multiple individual pathways for the transduction of different apoptotic signals, but rather were defective in a common event(s) that was induced by many apoptotic signal transduction pathways.…”
Section: Introductionmentioning
confidence: 98%
“…There are both pro-(bad, bax, bak, bik, hrk, bcl-XS) and antiapoptotic members (bcl-2, bcl-XL, Mcl-1) in this family although some genes may have contrasting e ects in di erent cell lines, during various stages of di erentiation, or phases of the cell cycle (Ray et al, 1996;O'Reilly et al, 1996). Alterations in expression of various bcl-2 family members can regulate tumorogenesis and response of cancer cells to cytotoxic therapies (Yang and Korsmeyer, 1996;Ealovega et al, 1996;Boise et al, 1993;Ray et al, 1996;Han et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This, coupled with the detection of varying levels of bcl-XS reported in normal colonic mucosa, adenomas and adenocarcinomas strengthen a possible role for this family of genes in the progression of neoplastic disease (Krajewska et al, 1996). Dysregulation of bcl-2 family members has been implicated in chemoresistance of numerous cancers, including colorectal tumors, in which lack of the wild-type p53 transcriptional induction of bax and inhibition of bcl-2 may desensitize these cells to various insults (Miyashita et al, 1994;Zhan et al, 1994;Sinicrope et al, 1995;Ibrado et al, 1996;Han et al, 1996;Boise et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been established that p21 deficient cells are unable to arrest in G 1 following irradiation, yet loss of p21 in intestinal epithelial cells does not prevent p53-dependent apoptosis in response to irradiation (Brugarolos et al, 1995). In addition in p53 deficient cells, radiation-induced apoptosis can occur in association with a G 2 /M arrest (Han et al, 1995, Allday et al, 1995.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand no G 1 arrest is observed when p53 is mutated, and apoptosis can be prevented under these conditions (Lotem andSachs, 1993, Bae et al, 1995). While p53 is frequently mutated in Burkitt's lymphoma cell lines (Farrell et al, 1991), recent evidence suggests that even in the absence of functional protein, cells maintain sensitivity to radiation-induced apoptosis through a p53-independent pathway associated with G 2 /M arrest (Allday et al, 1995, Han et al, 1995, Khanna et al, 1996. The radiation signal transduction pathway operating through p53 is now well described (Kastan et al, 1991;Dulic et al, 1994) being responsible for inducing p21 WAF1 and GADD45 genes involved in cell cycle control and DNA repair (Fornace et al, 1992.…”
Section: Introductionmentioning
confidence: 99%